Becoming an academic writer : 50 exercises for paced, productive, and powerful writing - Goodson, Patricia 1958- (SAGE, 2017)
Summary: Becoming an Academic Writer helps academic writers by providing the tools they need to gain control over writing and publishing, master specific aspects of academic writing, and improve their productivity. Author Patricia Goodson offers weekly exercises and tools to achieve these goals. The exercises are grounded in a theoretically sound and empirically based model comprising a set of behavioral principles (e.g., writing regularly, separating generating from editing) and specific practices (weekly exercises) that ensure success.